Everyday statistical reasoning - Lawson, Timothy J. (Wadsworth/Thomson Learning, 2002)
Lawson uses scientific research and interesting examples to explain to students how statistical concepts can be applied to everyday decisions and judgements. Practical, user-friendly discussion of topics such as probability, correlation, and covariance help students make the connections between statistical concepts and the work they do in their psychology courses and labs